2013
DOI: 10.1111/ajt.12130
|View full text |Cite
|
Sign up to set email alerts
|

Complement Mediated Renal Inflammation Induced by Donor Brain Death: Role of Renal C5a-C5aR Interaction

Abstract: Kidneys retrieved from brain-dead donors have impaired allograft function after transplantation compared to kidneys from living donors. Donor brain death (BD) triggers inflammatory responses, including both systemic and local complement activation. The mechanism by which systemic activated complement contributes to allograft injury remains to be elucidated. The aim of this study was to investigate systemic C5a release after BD in human donors and direct effects of C5a on human renal tissue. C5a levels were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 34 publications
0
43
2
Order By: Relevance
“…Whole genome expression profiling of 53 human renal allograft protocol biopsies obtained at implantation confirmed significantly higher expression levels of complement genes in deceased donor kidneys (29). Extending these findings prior to surgical removal of the donor organ, van Werkhoven et al found that brain death initiates systemic complement activation, upregulates C5aR expression in renal tubular cells (30), and is associated with induction of intrarenal inflammatory cytokines. The authors hypothesized that complement activation that occurs in the donor accounts in part for the poorer outcomes of grafts harvested from deceased compared with living donors.…”
Section: Figurementioning
confidence: 92%
“…Whole genome expression profiling of 53 human renal allograft protocol biopsies obtained at implantation confirmed significantly higher expression levels of complement genes in deceased donor kidneys (29). Extending these findings prior to surgical removal of the donor organ, van Werkhoven et al found that brain death initiates systemic complement activation, upregulates C5aR expression in renal tubular cells (30), and is associated with induction of intrarenal inflammatory cytokines. The authors hypothesized that complement activation that occurs in the donor accounts in part for the poorer outcomes of grafts harvested from deceased compared with living donors.…”
Section: Figurementioning
confidence: 92%
“…In the brain-deceased donor, the intracranial hypertension triggers a massive release of cytokines and growth factors with consequent activation of cell-adhesion molecules and leukocyte infiltration in the kidney [34]. Another consequence of brain death is local upregulation and the activation of complement that can contribute to create an inflammatory environment [35]. The manipulation of the kidney during removal may also produce mechanical injury.…”
Section: Innate Immunity Activation In Kidney Allotransplantationmentioning
confidence: 99%
“…In a similar study, Damman et al reported that high levels of the terminal MAC in the plasma of brain-dead donors was strongly associated with acute rejection within the first year post-transplantation [57]. Additionally, activation of the C5a-C5aR axis in kidney donors plays an important role in the amplification of the inflammatory response to brain death [58]. …”
Section: Reviewmentioning
confidence: 99%
“…As described earlier, anaphylatoxin C5a and signaling through the C5aR play pivotal roles in mediating IRI and the dysregulated inflammatory response in the brain-dead donor [38,58]. Furthermore, the use of C5a receptor antagonists has been effective in attenuating the extent of IRI in small animal models and limiting fibrogenic responses after acute kidney injury [39,78,104].…”
Section: Reviewmentioning
confidence: 99%